Construction of Endo-Functionalized Two Dimensional Metallacycles via Coordination-Driven Self-Assembly - Zhao, Liang (2009)
[Image: see text] The synthesis of three endofunctionalized two-dimensional supramolecular metallacycles including two [2 + 2] rhomboids (5 and 6) and a [3 + 3] hexagon (7) is reported. The resulting self-assembled supramolecular structures, containing several nitrobenzyl moieties at their interior surface, have been fully characterized by multinuclear NMR ((31)P and (1)H) and electrospray ionization mass spectrometry. A significant C–H…O hydrogen bonding between the nitrobenzyl acceptor and the edge molecules of the supramolecular architecture is observed in the small rhomboid 5 and this interaction gradually decreases upon the enlargement of the resulting polygonal structures from a small rhomboid 5 through a large rhomboid 6 to a hexagon 7. Molecular modeling with the MMFF force field gives a possible conformation of each self-assembly in different solvents and shows that the hydrophilic nitrobenzyl moiety prefers to be buried in the cavity of the resulting polygonal structures in nonpolar solvents, thus forming hydrogen bonds with the peripheral component building units.